Rodzicielstwo osób z niepełnosprawnością intelektualną – od akceptacji do wsparcia - Drzazga, Agnieszka (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2016)
Parenthood of people with intellectual disability is still a controversial issue but cannot be avoided because many of them want to have families and be parents. Altogether with introducing the idea of normalization, integration and empowerment they strive more and more intensively for their right to “normal” life. The main doubt is if they can be good parents. Previously the opinion was that intellectual disability makes it impossible and that their children are always in danger of poorer environment, neglect of their needs or abuse. Now factors influencing parenthood abilities are better identified. They are: socio-economic status, family functioning, parents' physical and mental health, child characteristics, social factors and others. Nowadays the main question is not if people with intellectual disability can be parents but how to support them to be good parents.